Research of Conceptual Design and Kinematic Characteristic of a 3-PRS Parallel Kinematic Machine - Tang Tengfei; Zhang Jun (Jixie chuandong)
A conceptual design of a parallel kinematic machine（ PKM） whose topological arrangement is a 3-PRS parallel mechanism is proposed. Based on the screw theory,the degree of freedom（ DOF） of the proposed PKM is analyzed. The results show that the 3-PRS PKM possesses one translational and two rotational capabilities（ 1T2R）. After the DOF analysis,a kinematics model is established. By solving the closed-loop vector motion equation,the analytical expression for the inverse kinematics solution of the proposed 3-PRS PKM is given. Based on the inverse kinematics solution,by considering the geometrical constraints,the reachable workspace search process is constructed,and the reachable workspace mapping of 3-PRS PKM is given. Finally,a sensitivity analysis is carried out to reveal the influences of some major dimensional parameters on the reachable workspace of 3-PRS PKM. The research results manifest that these dimensional parameters have different influences on the reachable workspace of 3-PRS PKM. Among all these parameters,the radius of the moving platform should be paid more attentions during the dimension synthesis of PKM.